2020
DOI: 10.1063/5.0004423
|View full text |Cite
|
Sign up to set email alerts
|

Study of single-layer stacking faults in 4H–SiC by deep level transient spectroscopy

Abstract: The electronic properties of single-layer Shockley-type stacking faults (SSFs) in 4H–SiC have been studied by deep level transient spectroscopy (DLTS) in the temperature range from 80 to 300 K. SSFs are introduced by low energy electron beam irradiation at room temperature using intentionally made scratches as nucleation sites. A DLTS peak was detected after SSF nucleation and expansion, the amplitude of which decreases after SSF shrinking. For the SSF energy level, a value of 0.213 ± 0.005 eV below the conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…As discussed above, it is widely accepted that this driving force is provided by QWA [6,9,18,[34][35][36]. However, a calculation shows that for the binding energy of 0.213 eV [48] and the equilibrium carrier concentration the energy gain due to the electron capture into SSFs is insufficient to exceed the SSF formation energy and to provide the driving force even if the recent value for the SSF formation energy of 4.7 mJ m −2 [20] is used. The same conclusion was also made in [36,49], in which it was shown that the threshold carrier density at room temperature was higher than 10 17 cm −3 that contradicts the numerous experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, it is widely accepted that this driving force is provided by QWA [6,9,18,[34][35][36]. However, a calculation shows that for the binding energy of 0.213 eV [48] and the equilibrium carrier concentration the energy gain due to the electron capture into SSFs is insufficient to exceed the SSF formation energy and to provide the driving force even if the recent value for the SSF formation energy of 4.7 mJ m −2 [20] is used. The same conclusion was also made in [36,49], in which it was shown that the threshold carrier density at room temperature was higher than 10 17 cm −3 that contradicts the numerous experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…Although the energy level of 'C' points to a Ti peak according to [20], an origin related to an impurity is contradicted by the appearance of 'C' only after irradiation for DUT 3. Interestingly, a DLTS peak with similar parameters ([EV + Ea] = 0.213 ± 0.005 eV, 𝜎 𝑝 = 7 × 10 −15 cm 2 ) to the 'C' peak has been found in [21] and attributed to single-layer Shockley-type stacking faults. Further investigation is needed to establish whether the 'C' peak originates from extended defects.…”
Section: Arrhenius Analysismentioning
confidence: 70%
“…Another type of SFs was in-grown SFs, which were produced during epitaxial growth and had no relationship with substrate quality. At present, most epitaxial SFs belong to the second type, and most of these faults were Shockley SFs, which are generated by sliding in the basal plane [111][112][113][114]. On one hand, Frank-type SFs were created by the addition or removal of Si-C bilayers, which typically generated due to polycrystalline instability at the initial growth stage, while Shockley-type SFs referred with the C-core and Si-core dislocations were originated from the depolymerization of BPDs.…”
Section: Plane Defectsmentioning
confidence: 99%